First-principles study of CO2 hydrogenation to formic acid on single-atom catalysts supported on SiO2. Issue 33 (15th August 2022) - Sun, Jikai; Jiang, Shuchao; Zhao, Yanliang; Wang, Honglei; Zhai, Dong; Deng, Weiqiao; Sun, Lei
Abstract : Schematic diagram of hydrogen spillover and CO2 hydrogenation on SiO2 surface. Abstract : The hydrogenation of CO2 into valuable chemical fuels reduces the atmospheric CO2 content and also has broad economic prospects. Support is essential for catalysts, but many of the reported support materials cannot meet the requirements of accessibility and durability. Herein, we theoretically designed a series of single-atom noble metals anchored on a SiO2 surface for CO2 hydrogenation using density functional theory (DFT) calculations. Through theoretical evaluation of the formation energy, hydrogen dissociation capacity, and activity of CO2 hydrogenation, we found that Ru@SiO2 is a promising candidate for CO2 hydrogenation to formic acid. The energy barrier of the rate-determining step of the entire conversion process is 23.9 kcal mol −1 ; thus, the reaction can occur under mild conditions. In addition, active and stable origins were revealed through electronic structure analysis. The charge of the metal atom is a good descriptor of the catalytic activity. The Pearson correlation coefficient (PCC) between metal charge and its CO2 hydrogenation barrier is 0.99. Two solvent models were also used to investigate hydrogen spillover processes and the reaction path was searched by the climbing image nudged-elastic-band (CI-NEB) method. The results indicated that the explicit solvent model could not be simplified into a few solvent molecules, leading to a large difference in the reaction paths. This work will serve as a reference for the future design of more efficient catalysts for CO2 hydrogenation.